Negotiation of Tradition, Islam, and Modernity in the Kaum Mudo Islamic Reform Movement in Minangkabau - Andri Ashadi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
At the beginning of the 20th century, when the modernism of Islam was strengthened in Minangkabau, many academics viewed the Kaum Mudo movement paradoxically. On the one hand, it was considered to be progress-oriented by negotiating and accommodating adat, and as such, the followers were referred to as reformers. Conversely, the movement was seen as opposing and eliminating against the elemental integration of local cultures or adat and modern ideas into Islam. Hence, the supporters were also referred to as puritans. This article employed Stella Ting-Toomeys’s identity negotiation theory, which refers to ethnic or traditional and religious identities as primary. Consequently, it was concluded that the Kaum Mudo Islamic reform movement in Minangkabau was rooted in religious customs and traditions and not purification. Furthermore, it was observed in several cases, such as the contests and fights for mutual influence by the existing social groups. It was also seen in the ethnic backgrounds of each character at times when attitudes, which give room for negotiations, are required. Meanwhile, the existing madrasa reform models negotiated between the traditional surau system and the modern Dutch school have displayed this movement. Finally, the existence of a synthesis of adat with Islam and modernity in Minangkabau, which are engaged in mutual negotiations, was also seen.